2017
DOI: 10.21608/ejnf.2017.75219
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Lambs Fed Rations Supplemented With Thyme Essential Oil

Abstract: ighteen growing Ossimi lambs (28.92 kg average live body weight and 6-7 months old) were used to evaluate incorporating thyme essential oil (TEO) in ration on nutrients digestibility and growth performance. In growth trial lasted 90 days followed by digestibility trial for 14 days, the lambs were randomly divided according to their live body weight into three feeding groups (6 each).Total mixed ration consisted of 60% concentrate: 40% roughage was offered to lambs in all groups to cover its total requirements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Whatever its concentration significantly decreased (P<0.05) with increasing the addition of ajwain seeds, this decrease may be due to that some essential oils included in the seeds have activity impact antihyper-NH 3producing ruminal bacteria such as Peptostreptococcus anaerobic and as Clostridium astyklandy (6,7,20), also may be regarded to protein binding substances existing in ajwain seeds like tannins which might be reduced dietary protein degradability (11). The same results for the decreasing of ammonia nitrogen concentration were recorded by fistulated buffalo fed various parts of the ajwain plant (30) and with lambs fed diets supplemented with thyme essential oil (14). The overall mean of rumen total volatile fatty acids significantly (P<0.05) increased linearly with T2 and T3 by 4.21 and 18.72 %, respectively compared with T1.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Whatever its concentration significantly decreased (P<0.05) with increasing the addition of ajwain seeds, this decrease may be due to that some essential oils included in the seeds have activity impact antihyper-NH 3producing ruminal bacteria such as Peptostreptococcus anaerobic and as Clostridium astyklandy (6,7,20), also may be regarded to protein binding substances existing in ajwain seeds like tannins which might be reduced dietary protein degradability (11). The same results for the decreasing of ammonia nitrogen concentration were recorded by fistulated buffalo fed various parts of the ajwain plant (30) and with lambs fed diets supplemented with thyme essential oil (14). The overall mean of rumen total volatile fatty acids significantly (P<0.05) increased linearly with T2 and T3 by 4.21 and 18.72 %, respectively compared with T1.…”
Section: Resultsmentioning
confidence: 66%
“…Data in Table 4 showed that there were no significant differences among groups in the initial and final body weight of lambs fed experimental rations, however adding ajwain seeds significantly (P<0.05) increased average daily gain by 12.76 and 17.70 %, respectively compared with those fed T1. These increases might be attributed to the high TDN and nutrient digestibility with T2 and T3, regarding to the presence content of essential oils in ajwain seed which increases the energy availability for animals (14,39). Adding ajwain seed in the basal ration did not show any impact on feed intake.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers and breeders are searching for feed additives to improve animal performance, nutritional content, and eventually carcass qualities. Extracts from known herbs, as garlic, clove, thyme, turmeric, and cinnamon can be utilized as natural feed supplement in livestock feed (El-Naggar et al, 2017). The biological properties of herbal phytochemical compounds, or their extracts, are beneficial to the health and contributes to improve animal performance, intestinal microbiota, antioxidant capacity, antimicrobial, antibiotic, cholesterol reduction, immune modulatory, and eventually in enhancing carcass characteristics and quality of meat to the human as the end consumer, (Elsherif et al, 2021;Lamiaa et al, 2022).…”
Section: Advances Inmentioning
confidence: 99%
“…Additionally, thyme contains antibacterial and antioxidant characteristics. This is mostly because of its active ingredients such as thymol, phenols and carvacrol, which also increase appetite and have been shown to support growth performance (El-Naggar et al 2017;Raskovic et al, 2015).…”
Section: Advances Inmentioning
confidence: 99%
“…Nowadays, numerous feed additives are available and efficiently used in the daily feeding practices of beef and dairy farm stations. Unsaturated fatty acids, essential-sulfur-containing amino acids, vitamins, chelated minerals, organic acids, ionophores, probiotics (Helal et al, 2021), prebiotics, and plant extracts and their secondary metabolites (El-Naggar et al 2017a), all are being used as feed supplements to enhance feed utilization and promote animal productivity (Soliva et al 2005;. In tropical and subtropical regions where good quality forages are scarcely available, so the use of fodder trees, browses and shrubs had been confirmed for ruminant feeding (Benninson and I Paterson, 2003).…”
Section: Introductionmentioning
confidence: 99%